A method for modelling of parameter estimation laws depending on functions for adaptive control of robot manipulators. (27th September 2011) - Burkan, Recep
In this paper, first, a new method for modelling of adaptive control laws for controlling robot manipulators is presented. Then, based on the Lyapunov theory, we have proposed five new adaptive control laws thus, stability of uncertain system is guaranteed. Based on previous studies, adaptive control laws are derived from Lyapunov theory using some different functions depending on tracking error, robot inertia and kinematics parameters. This study also shows not only that adaptive controllers cover these derivations but also that it would be possible to derive another parameter adaptive law based on this study providing that appropriate function is chosen. Application to a two-link robotic manipulator is presented. Numerical simulation results are included.